Planning the Patient Safety Management System Using Failure Mode and Effect Analysis in ICU Care: A Case Study in Loghman Hakim Hospital Shahid Beheshti University of Medical Sciences in Tehran city - sima marzban; mahshid Moeini Naini; Sayed hossein Ardehali; jaber hekmatyar; aliamir Savadkouhi (Tehran University of Medical Sciences, 2017)
Background: Injuries related to failures and errors due to clinical interventions in patient hospitalization period in hospital are the main reasons of mortality and mortality in worldwide. This study tries to identify and description ICU care failures and assessing the causes of risks, Severity, Occurrence and identifying risk probability ratio and risk prioritizing using FMEA method. Materials and Methods: This study was carried out in order to evaluating existing situation using Failure Mode and Effect Analysis and utilizes volere logic to plan the patient safety management system. This study performed in the intensive care unit of Loghman Hakim hospital in Iran. Results: Study finding revealed sixteen routine failures and its priorities which the five main issues were documented as error in decision phase for patients admission or in-admission (PRN 1000), error in discharge time of patient from ICU (PRN 1000), insufficient infection control (PRN 1000) and error in clinical ordering and prescriptions (PRN 800). Conclusion: The main requirements of the patient safety management identified as planning standards and clinical guidelines, developing evidence based admission and non admission indicators, enacting infection control rules and education of anticipating standards places, hand washing and disinfecting instrument and equipments.